From dynamic risk factors to causal processes: a methodological framework. Issue 1 (22nd January 2016) - Ward, Tony; Fortune, Clare-Ann
ABSTRACT: It is becoming increasingly apparent that dynamic risk factors are unable to function as explanations of offending because they are composite constructs, which contain a mixture of putative causes, states of affairs, and problematic cognitive, affective, behavioural and social states associated with crime. In this paper we draw from psychopathology research and theory on the conception and classification of mental disorders to develop the Dynamic Risk Research Framework (DRRF). In our opinion, the assumptions and methodological tool associated with this framework can better focus research into the causes of offending by making use of the information provided by dynamic risk factors. A conceptual framework such as the DRRF can arguably translate this valuable information into deep, coherent explanations, and ultimately, more streamlined and precise intervention strategies.